Incidence of Herbal Use among Pregnant Women Attending Family Care Center - Omar Bassam Ahmad Saleh, Anam Nasir, Najma Fatima, Sobia Aamir, Tooba Jamal, Iqra Zulfiqar (Pakistan Journal of Medical & Health Sciences, 2022)
Background and Aim: Numerous investigations around the globe verified the increasing trend of medicine and complementary use in pregnant women. Pregnant women are not informed of potential teratogenic effects from traditional medicines; some herbal products may cause birth defects in humans. Pregnant women’s use of traditional medicine has not yet been evaluated in Pakistan. The present study aimed to determine the incidence of herbal use among pregnant women attending family care centers. Material and Methods: This hospital-based cross-sectional study was conducted on 320 pregnant women attending Family care centers in Jamshoro Hyderabad and Mirpur AJK for the duration of six months from January 2022 to June 2022. Pregnant women attending antenatal care and volunteering to respond were enrolled and those with mental illness and were unwilling to respond were excluded. Herbal medicine self-medication was a dependent variable whereas gestational age, sociodemographic details, and herbal medicine history were independent variables. A questionnaire was designed for determining prior history of herbal use, types of herbal medicine, herbal used in current pregnancy. SPSS version 26 was used for data analysis. Results: Of the total 320 pregnant women, the incidence of herbal use was 86 (26.9%). Based on age, pregnant women were grouped as follows: 64 (20%) in 17-25 years, 148 (46.2%) in 26-35 years, and 108 (33.8%) 35-45 years. The prevalence of herbal usage in the first, second, and third trimesters was 62 (72.1%), 9 (10.5%), and 8 (9.3%), respectively, among 86 herbal-using pregnant women. About 7 (8.1%) pregnant women used herbs in all trimesters. Garlic (Allium sativum) 32 (37.2%), Ginger (zingiberofcinale) 40 (46.5%), Eucalyptus 6 (7%), and tenaadam 8 (9.3%) were different types of herbs used by pregnant women. Conclusion: The present study found that about 26.9% pregnant women used herbal medicine during pregnancy. Majority of women used herbal medicine in the first trimester followed by second and third. Ginger was the most commonly used herbal medicine followed by garlic and tenaadam. Nausea, morning sickness, and vomiting was the most prevalent clinical indications. Keywords: Herbal Medicine, Prevalence, Trimester, Pregnant women